2008
DOI: 10.1017/s1355617708080946
|View full text |Cite
|
Sign up to set email alerts
|

Stroop performance in multiple sclerosis: Information processing, selective attention, or executive functioning?

Abstract: Cognitive impairments in information processing speed, attention and executive functioning are widely reported in patients with multiple sclerosis (MS). Several studies have identified impaired performance on the Stroop test in people with MS, yet uncertainty remains over the cause of this phenomenon. In this study, 25 patients with MS were assessed with a neuropsychological test battery including a computerized Stroop test and a computerized test of information processing speed, the Graded Conditional Discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 49 publications
(86 reference statements)
3
39
0
5
Order By: Relevance
“…The Stroop task was chosen because previous studies had identified that people with MS exhibit delayed Stroop responses compared to subjects without MS, even in mild stages of the disease [28][29][30][31][32]. These other studies, however, generally employed a more complex visual color-word paradigm with more than two response choices, whereas our study employed a twochoice auditory Stroop paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…The Stroop task was chosen because previous studies had identified that people with MS exhibit delayed Stroop responses compared to subjects without MS, even in mild stages of the disease [28][29][30][31][32]. These other studies, however, generally employed a more complex visual color-word paradigm with more than two response choices, whereas our study employed a twochoice auditory Stroop paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…This task has been described in detail elsewhere and has been validated for use with MS patients (Denney, Gallagher, & Lynch, 2011). Slower performance by MS patients on this task has been shown to be due to slowed processing speed (Macniven et al, 2008). The variable of interest was a composite score derived from the total number of correct responses on the word reading and color naming trials.…”
Section: Processing Speed/attention Measuresmentioning
confidence: 99%
“…In two such studies, processing speed abilities were found to be associated with performance on tasks on the DKEFS, as well as the Stroop test (Drew, Starkey, & Isler, 2009; Macniven et al, 2008). (Drew et al, 2009) reported that processing speed measures were significantly correlated with both timed and untimed measures of the DKEFS, including Trail-Making Test, Verbal-Fluency, Card-Sorting and Proverbs.…”
Section: Introductionmentioning
confidence: 99%